Existence of positive solutions for a singular fractional boundary value problem - Henderson, Johnny; Luca, Rodica (Nonlinear Analysis: Modelling and Control, 2017)
We study the existence of positive solutions for a nonlinear Riemann–Liouville fractional differential equation with a sign-changing nonlinearity, subject to multi-point fractional boundary conditions.
Keywords: Riemann–Liouville fractional differential equation; fractional boundary conditions; positive solutions; sign-changing nonlinearity